Cardiometabolic correlates of sleep disordered breathing in Andean highlanders. Issue 6 (15th June 2017) - Pham, Luu V.; Miele, Catherine H.; Schwartz, Noah G.; Arias, Rafael S.; Rattner, Adi; Gilman, Robert H.; Miranda, J. Jaime; Polotsky, Vsevolod Y.; Checkley, William; Schwartz, Alan R.
Associations between sleep disordered breathing (SDB) and cardiometabolic outcomes have not been examined in highlanders. We performed nocturnal polygraphy in Peruvian highlanders (3825 m). Multivariable linear regression models examined associations between SDB metrics and haemoglobin, glucose tolerance (haemoglobin A1c (HbA1c)), fasting glucose, homeostatic model-based assessments of insulin resistance and β-cell function (HOMA-IR and HOMA-β, respectively), blood pressure, and lipids, while adjusting for age, sex, body mass index (BMI) and wake oxygenation. Participants (n=187; 91 men) were (median (interquartile range)) 52 (45–62) years old, and had a BMI of 27.0 (24.3–29.5) kg·m −2 and 87% (85–88%) oxyhaemoglobin (arterial oxygen) saturation during wakefulness. In fully adjusted models, worsening nocturnal hypoxaemia was associated with haemoglobin elevations in men (p=0.03), independent of wake oxygenation and apnoea–hypopnoea index (AHI), whereas worsening wake oxygenation was associated with haemoglobin elevations in older women (p=0.02). In contrast, AHI was independently associated with HbA1c elevations (p<0.05). In single-variable models, nocturnal hypoxaemia was associated with higher HbA1c, HOMA-IR and HOMA-β (p<0.001, p=0.02 and p=0.04, respectively), whereas AHI was associated with HOMA-IR, systolic blood pressure and triglyceride elevations (p=0.02, p=0.01 and p<0.01, respectively). These associations were not significant in fully adjusted models. In highlanders, nocturnal hypoxaemia and sleep apnoea were associated with distinct cardiometabolic outcomes, conferring differential risk for excessive erythrocytosis and glucose intolerance, respectively. In highlanders, nocturnal hypoxaemia and sleep apnoea were associated with differential outcomes http://ow.ly/1k6z309MyDR